Analisis jenis makanan ikan sidat (Anguilla spp.) di Sungai Air Manna Bengkulu Selatan - Subhecty Reselta; Dede Hartono; Dewi Purnama (UNU Purwokerto, 2021)
Eel (Anguilla spp.) is catadromous with high economic values. Research on the analysis of eel's stomach contents provides information on its food and feeding habits. This study aimed to analyze the type, volume, frequency, and index of food preponderance of eel in the Manna River based on its length and weight. The method used in this research is a survey method by collecting samples of eels by purposive sampling. Sampling was carried out in September 2019. The results showed the eels ate five types of food: crabs, shrimps, insect larvae, plankton, and litter. Based on the food volume (Vi), crab kinds were the most commonly eaten by the eels. The food-frequency of occurrence (Oi) for eel is most often found in the types of crabs, shrimps, and plankton. Index of Preponderance (IP) showed that this eel's main food was crabs, while the complimentary food was shrimps, insect larvae, and plankton. Litter, on the other side, was an addition to all types of food obtained.